Solvent-free production of thermoplastic lignocellulose from wood pulp by reactive extrusion - Li, Jinlei; Baker, Thomas; Sacripante, Guerino; Lawton, David; Marway, Heera; Zhang, Hongfeng; Thompson, Michael (Carbohydrate Polymers, 2021)
A novel acylation approach suited to rapid bulk thermoplasticization of lignocellulose without solvents was previously demonstrated by the authors in benchtop batch studies. The method relies upon a benzethonium chloride/sulfuric acid functionalizing agent at low concentrations to act as a wetting agent for the wood pulp, similar to an ionic liquid, yet binds to the lignocellulose ester as a flow aid in the final thermoplastic. The present investigation evaluates the approach in a residence time-limited (45-90 s) continuous twin-screw reactor, where intensive mixing and heat were found to yield high acylation. The modified lignocellulose exhibited desired thermoplasticity by being melt moldable without the need for plasticizers and maintained much of the excellent stiffness of cellulose, demonstrating a maximum flexural modulus of 5.4 GPa and tensile modulus of 1.8 GPa. The influence of extrusion conditions on thermoplasticity was examined by a Design of Experiments (DOE) analysis.